Carbonic Anhydrase III Is Expressed in Mouse Skeletal Muscles Independent of Fiber Type-Specific Myofilament Protein Isoforms and Plays a Role in Fatigue Resistance - Feng, Han-Zhong; Jin, J.-P. (Frontiers in Physiology, 2016)
Carbonic anhydrase III (CAIII) is a metabolic enzyme and a regulator for intracellular pH. CAIII has been reported with high level expression in slow twitch skeletal muscles. Here we demonstrate that CAIII is expressed in multiple slow and fast twitch muscles of adult mouse independent of the expression of myosin isoforms. Expressing similar fast type of myofilament proteins, CAIII-positive tibial anterior (TA) muscle exhibits higher tolerance to fatigue than that of CAIII-negative fast twitch extensor digitorum longus (EDL) muscle in in situ contractility studies. We further studied the muscles of CAIII knockout (Car3-KO) mice. The loss of CAIII in soleus and TA muscles in Car3-KO mice did not change muscle mass, sarcomere protein isoform contents, and the baseline twitch and tetanic contractility as compared with age-matched wild type (WT) controls. On the other hand, Car3-KO TA muscle showed faster force reduction at the beginning but higher resistance at the end during a fatigue test, followed by slower post fatigue recovery than that of WT TA muscle. Superfused Car3-KO soleus muscle also had faster total force reduction during fatigue test than that of WT soleus. However, it showed a less elevation of resting tension followed by a better post fatigue recovery under acidotic stress. CAIII was detected in neonatal TA and EDL muscle, downregulated during development, and then re-expressed in adult TA but not EDL muscles. The expression of CAIII in Tnnt1-KO myopathy mouse soleus muscle that has diminished slow fiber contents due to the loss of slow troponin T remained high. Car3-KO EDL, TA and soleus muscles showed no change in the expression of mitochondria biomarker proteins. The data suggest a fiber type independent expression of CAIII in with a role in the regulation of intracellular pH in skeletal muscle and may be explored as a target for improving fatigue resistance and for the treatment of TNNT1 myopathies.